Pengangguran , Pendidikan , Inflasi dan Kemiskinan di Indonesia Periode Tahun 2014-2020 - Findianingsih, Arisa; Sulasih, Sulasih; Shafrani, Yoiz Shofwa; Novandari, Weni (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2023)
The aim of this research is to determine the influence of unemployment, education and inflation on poverty in Indonesia for the 2014-2020 period, either partially or simultaneously. Type of quantitative research with secondary data sources, namely those originating from the Central Statistics Agency (BPS). The total population of 34 provinces in Indonesia, the entire population was used as a sample or saturated sample. Meanwhile, the data analysis technique is multiple regression analysis. The results of this research show that the unemployment and inflation variables partially have a positive and significant effect on poverty in Indonesia for the 2014-2020 period with a t-count value of 2.326 > 1.6586 (t-table) and a significance value of 0.022 < alpha (0, 05) and the t-count value is 2.118 > 1.6586 (t-table) and the significance value is 0.036 > alpha (0.05). Meanwhile, the education variable partially has no effect on poverty in Indonesia for the 2014-2020 period because the t-count value is 1.486 < 1.6586 (t-table) and the significance value is 0.140 > alpha (0.05). Simultaneously, unemployment, education and inflation have a positive and significant effect on poverty in Indonesia for the 2014-2020 period with an f-count value of 909.066 > 2.686 (F-table) with a significance value of 0.000 < alpha (0.05).